Studies on the biological role of dna methylation; IV. Mode of methylation of DNA in E. coli cells. - Razin, A (1980)
Two pairs of restriction enzyme isoschizomers were used to study in vivo methylation of E. coli and extrachromosomal DNA. By use of the restriction enzymes MboI (which cleaves only the unmethylated GATC sequence) and its isoschizomer Sau3A (indifferent to methylated adenine at this sequence), we found that all the GATC sites in E. coli and in extrachromosomal DNAs are symmetrically methylated on both strands. The calculated number of GATC sites in E. coli DNA can account for all its m6Ade residues. Foreign DNA, like mouse mtDNA, which is not methylated at GATC sites became fully methylated at these sequences when introduced by transfection into E. coli cells. This experiment provides the first evidence for the operation of a de novo methylation mechanism for E. coli methylases not involved in restriction modification. When the two restriction enzyme isoschizomers, EcoRII and ApyI, were used to analyze the methylation pattern of CCTAGG sequences in E. coli C and phi X174 DNA, it was found that all these sites are methylated. The number of CCTAGG sites in E. coli C DNA does not account for all m5Cyt residues.